Marketing communication effectiveness of Philately Bureau Pos Malaysia Kota Kinabalu / Norhayati Othman - Othman, Norhayati (2009)
These studies were conduct to verify the effectiveness of marketing communication of philately product in the effort to promote those products among the students. The scope of a study is focused on the effectiveness of marketing communications of philately product among the students as the young people is the one that may contribute a lot on the philately sales of Pos Malaysia. Nowadays, with the emergence of IT that bringing together a lot of software programs that offers many thing such as internet and games influence the social activity among the young people especially student in the way their spend they spare time. We cannot refute that IT were bringing big impact to the social life of people. The terms of philately alone has a bit strange to the students unless with further information or definition, so there must be an effective's communication in order to encourage students to be a stamps collector or be a philately member. As a solely company that produce philately product there a must for Pos Malaysia to provide quality product and services including marketing communication tool to the present customer or new customer. It's not only to maintain and increase sale but at the same time to assured that philately product still competitive in the modern life and in the IT era.